Employment contracts, conditions, and the relationship of employment - English, J (Sweet and Maxwell, 2023)
Considers the nature of an employee's entitlement to claim, and the employer's obligation to pay, a salary or wages, and why an employee who refuses to accept a wrongful dismissal by their employer and decides to keep the contract open is unable to sue in debt for their salary or wages.